An experimental and modelling study of heat loads on a subscale methane rocket motor. (November 2019) - Hong, Ye; Liu, Zhanyi; Silvestri, Simona; Celano, Maria P.; Haidn, Oskar J.; Yu, Zhendong
Abstract: Given growing competition in the business space launch market, more researchers are evaluating the merit of methane as a potential propellant. In this study, a rocket combustion chamber with a single coaxial shear injector is tested. Gaseous oxygen and gaseous methane are employed in the hot firing tests at 2 MPa and a mass ratio of oxidizer to fuel of 2.65. Along the chamber axis, the wall temperatures are recorded; an inverse heat conduction approach forms the basis of the wall heat flux calculations. By applying the solver ANSYS Fluent, numerical simulations offer a superior analysis of the results. To describe the turbulence-chemistry interactions, the eddy dissipation concept model is employed. Mesh independency has been verified with the objective of comparing the experimental data with the heat fluxes calculated from simulations, followed by additional analysis. To gain a more thorough understanding of the experimentally determined heat flux profile, the hot gas temperature distribution is also examined. As the comparison proves, this study's simulation approach predicts, with sufficient precision, wall heat fluxes in a rocket combustor. Highlights: The heat fluxes are obtained in an inverse heat conduction method. The heat flux profiles are acquired at each time step during the transient process. CFD simulations precisely predict the position of the peak of heat flux. Numerically calculated heat flux and pressure profiles agree well with experiments.